ANALYSIS OF TRAFFIC CHARACTERISTICS TOTAL VOLUME, ACTIONS, QUEUE LENGTH AND DEGREES OF SATISFACTION AT THE UNSIGNIFICANT JUNCTION JL SEMARANG-BOJA, SEMARANG - sentanu, arga; suwandi, putri anggi permata; yudaningrum, farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2023)
Unsignalized intersection Jl. Raya Cangkiran - Jl Cangkiran Gunung Pati, Tambangan kec.Mijen, Semarang is a three-way intersection that has access to the Cupan Terminal. Many people pass through this intersection. In conditions at these intersections, traffic jams occur during rush hours, and there is no traffic light which makes traffic conditions even more irregular, the safety of motorists is also threatened. Therefore, this study was carried out to analyze unsignalized intersections, planning the use of traffic lights, and knowing the traffic characteristics of Jl. Raya Cangkiran - Jl. Gunungpati Cup, Semarang. Data collection was carried out for 3 days, namely Saturday 25 February 2023, Monday 27 February 2023, and Wednesday, 1 March 2023 by taking peak hours at 06.00 WIB - 08.00 WIB, 12.00 WIB - 13.00 WIB, and 16.00 WIB - 18.00 WIB. Data collection methods used are capacity, degree of saturation, delays, queue opportunities, and Traffic Signaling Devices (APILL). The performance analysis of this unsignalized intersection uses the 1997 Indonesian Highway Capacity Manual (MKJI) to calculate the degree of saturation. As for the level of service using the Minister of Transportation Regulation No. 96 PM 2015. The results of the research are that in the existing conditions, alternative B is chosen as the best alternative for planning traffic lights with 2 phases of the 1-hour peak scenario on Saturday morning with a degree of saturation of 0.823 pcu/hour, a queue length of 103,045 m on the West approach, and a value delay of 14,784 veh/sec. From the results of the analysis, it can be concluded that the results of calculating the traffic evaluation for the current conditions obtained that the highest vehicle volume occurred on Monday, 27 February 2023. Then Jl. Raya Cangkiran – Boja, Semarang, fulfills the criteria for installing traffic lights and needs to install traffic lights or traffic control lights. As well as from the 3 planned alternatives, alternative B was chosen to install a 2-phase traffic signal light.